Issues on Halal Foods with Special Reference to Fatwa on Halal Pet Food for Cats in Islamic Law - Nurdeng Deuraseh; Nurulhuda Asilah Asli (El-Mashlahah, 2022)
When it comes to pet food, halal issues rarely arise. However, several people care about this issue. This is because humans have evolved from a time when animals did not live with humans to when it was found that many families had at least one pet. Especially in the modern world, more and more pets have been considered an integral part of the family all over the world. Also, the increase in income of the Muslim population can change their lifestyle, and owning a pet is an integral part of the family. According to statistics made in the United States, more than half of all Americans have a dog or cat in their home. Meanwhile, 45% of households in Romania have a cat. And, 92% of cats in Australia are kept at home. This article aimed to discuss the need to provide halal food for pet cats according to Islamic law. Also, it provide debates and intellectual findings related to the issue of halal pet food to fill the literature gap. This research is normative legal research using the Islamic law approach. The results of this study indicate that it is safe to suggest based on research that if there is no pork in pet food and as long as it is guaranteed to be harmless and safe for pets to eat, then the food should not be a problem to eat, serve and provide for cats.